Inhibitory Regulation of Higher-Plant Myosin by Ca(2+) Ions - Yokota, Etsuo (American Society of Plant Physiologists, 1999)
Myosin isolated from the pollen tubes of lily (Lilium longiflorum) is composed of a 170-kD heavy chain (E. Yokota and T. Shimmen [1994] Protoplasma 177: 153–162). Both the motile activity in vitro and the F-actin-stimulated ATPase activity of this myosin were inhibited by Ca(2+) at concentrations higher than 10(−6) m. In the Ca(2+) range between 10(−6) and 10(−5) m, inhibition of the motile activity was reversible. In contrast, inhibition by more than 10(−5) m Ca(2+) was not reversible upon Ca(2+) removal. An 18-kD polypeptide that showed the same mobility in sodium dodecyl sulfate-polyacrylamide gel electrophoresis as that of spinach calmodulin (CaM) was present in this myosin fraction. This polypeptide showed a mobility shift in sodium dodecyl sulfate-polyacrylamide gel electrophoresis in a Ca(2+)-dependent manner. Furthermore, this polypeptide was recognized by antiserum against spinach CaM. By immunoprecipitation using antiserum against the 170-kD heavy chain, the 18-kD polypeptide was coprecipitated with the 170-kD heavy chain, provided that the Ca(2+) concentration was low, indicating that this 18-kD polypeptide is bound to the 170-kD myosin heavy chain. However, the 18-kD polypeptide was dissociated from the 170-kD heavy chain at high Ca(2+) concentrations, which irreversibly inhibited the motile activity of this myosin. From these results, it is suggested that the 18-kD polypeptide, which is likely to be CaM, is associated with the 170-kD heavy chain as a light chain. It is also suggested that this polypeptide is involved in the regulation of this myosin by Ca(2+). This is the first biochemical basis, to our knowledge, for Ca(2+) regulation of cytoplasmic streaming in higher plants.